Long-term risk of ectopic pregnancy varies by method of tubal sterilization: A whole-population study - Malacova, Eva; Kemp, A.; Hart, R.; Jama-Alol, K.; Preen, D. (Elsevier, 2014)
Objective To evaluate the risk of ectopic pregnancy (EP) associated with different methods of tubal sterilization. Design Population-based retrospective cohort study. Setting Hospitals in Western Australia. Patient(s) All women aged 18-44 years undergoing tubal sterilization between 1990 and 2010 at Western Australian hospitals (n = 44,829). Intervention(s) Data on tubal sterilization were extracted from hospital records. Main Outcome Measure(s) Long-term risk of EP. Result(s) There were 89 EPs recorded during the observation period in women previously sterilized. The 10-year and 15-year cumulative probability of EP for all methods of tubal sterilization were 2.4/1,000 and 2.9/1,000 procedures, respectively. The 10-year cumulative probability of EP was 3.5 times higher in women sterilized before the age of 28 years than in those sterilized after the age of 33 years. An increased risk of EP existed in women who received laparoscopic partial salpingectomy (adjusted hazard ratio = 14.57, 95% confidence interval 3.50-60.60) and electrodestruction (adjusted hazard ratio = 5.65, 95% confidence interval 2.38-13.40), compared with those who had laparoscopic unspecified destruction of fallopian tubes. Conclusion(s) Women undergoing tubal sterilization at a young age are at particular risk for subsequent EP. The risk among younger women doubled between 5 and 15 years after sterilization. Laparoscopic electrodestruction and partial salpingectomy carried the highest risk of EP. © 2014 American Society for Reproductive Medicine, Published by Elsevier Inc.